MATERNITY AND PARENTAL LEAVE: PRESENT AND PERSPECTIVES OF LEGAL TOOLS FOR HARMONIZING PROFESSIONAL AND FAMILY LIFE IN SLOVAKIA - Barinková, Milena (European Scientific Journal, ESJ, 2015)
The harmony of professional and family life is a permanent agenda item of various institutions of the European Union. Creating conditions for handling work obligations of employed parents without threatening their ability to fulfil their family obligations falls in the obligations of the member states based on minimum European legal standards. This article analyzes the effects of specific tools of employment legislation in Slovakia that aids parents of small children to combine the child care with the demands of wage labour. The results are based on an assessment of development of the current legislation, which reflects society’s priorities for the realization of economic and social policy, and which stem from the evaluation of the discussion in professional literature. Emphasis is also placed on reflections of perspectives and the need of redefining the legal conditions of the maternity and parental leave. The final outputs of this paper are de lege ferenda proposals in relation to the introduction of paternity leave and adoption leave.